Nonbacterial and bacterial osteomyelitis in children: a case-control retrospective study - Mikhail M. Kostik; Alexey S. Maletin; Veronika V. Petukhova; Veronika V. Petukhova; Alexander Yu. Mushkin; Alexander Yu. Mushkin (Frontiers Media S.A., 2023)
PurposeOsteomyelitis is a group of bone infectious (bacterial osteomyeilitis-BO) and noninfectious inflammatory diseases (nonbacterial osteomyelitis-NBO) with similar clinical, radiology, and laboratory features. Many patients with NBO are misdiagnosed as BO and receive unnecessary antibiotics and surgery. Our study aimed to compare clinical and laboratory features of NBO and BO in children, to define key discriminative criteria, and to create an NBO diagnostic score (NBODS).MethodsThe retrospective multicenter cohort study included clinical, laboratory, and instrumental information about histologically confirmed NBO (n = 91) and BO (n = 31). The variables allowed us to differentiate both conditions used to construct and validate the NBO DS.ResultsThe main differences between NBO and BO are as follows: onset age-7.3 (2.5; 10.6) vs. 10.5 (6.5; 12.7) years (p = 0.03), frequency of fever (34.1% vs. 90.6%, p = 0.0000001), symptomatic arthritis (67% vs. 28.1%, p = 0.0001), monofocal involvement (28.6% vs. 100%, p = 0.0000001), spine (32% vs. 6%, p = 0.004), femur (41% vs. 13%, p = 0.004), foot bones (40% vs. 13%, p = 0.005), clavicula (11% vs. 0%, p = 0.05), and sternum (11% vs. 0%, p = 0.039) involvement. The following four criteria are included in the NBO DS: CRP ≤ 55 mg/l (56 points), multifocal involvement (27 points), femur involvement (17 points), and neutrophil bands ≤ 220 cell/μl (15 points). The sum > 17 points allowed to differentiate NBO from BO with a sensitivity of 89.0% and a specificity of 96.9%.ConclusionThe diagnostic criteria may help discriminate NBO and BO and avoid excessive antibacterial treatment and surgery.